A New Analysis Detects Short Circuit Faults In 1 Phase Networks - Nico Karla Steven Purba; Septian Permana; Prayoga; Manganju Marpaung; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This paper is designed to detect the location of short circuit faults in a 1-phase electrical network system. The power supply source with a voltage of 12 V is converted into two voltage sources, namely positive voltage (+) and negative voltage (-), which are used to supply a parallel resistance circuit to measure the voltage difference. The voltage difference is forwarded to the op amp IC TL084 CN (using only 1 op amp). The output of the op amp is sent to the interface (ADC) to convert analogue signals into digital ones that can be received by a PC via an RS 232 cable or USB serial. After the data is received by the PC, the next step is data processing using the Visual Basic 6.0 application, which is carried out after the calibration process to ensure that the results obtained are accurate and reliable in detecting the location of short circuit faults precisely